Transformasi Pemasaran Konvensional Ke Digital Pada Umkm Kabupaten Kuningan Melalui Pendekatan Community Empowerment - Siti Amirah Makarim; R. Hozin Abdul Fatah; Akhmad Hidayat Nurul Akbar (CV. SINAR HOWUHOWU, 2026)
Micro, Small and Medium Enterprises (MSMEs) are the backbone of Indonesia's economy; however, most of them still rely on conventional marketing systems with limited reach. This community service activity aims to assist and empower MSME actors in Kuningan Regency in transforming their marketing from conventional to digital methods through a Community Empowerment approach. The methods used include: (1) initial MSME condition mapping, (2) intensive training and mentoring, and (3) continuous evaluation. This activity involved 45 MSME actors from 5 sub-districts in Kuningan Regency engaged in culinary, handicraft, and general trade sectors. The results showed a significant increase in MSME actors' understanding and ability in utilizing social media, marketplaces, and creating digital content. A total of 82% of participants successfully created active digital business accounts, 67% were able to create independent promotional content, and average revenue increased by 35% after three months of mentoring. The Community Empowerment approach proved effective because it positions the community as an active subject of transformation, not merely a training object. Program sustainability is ensured through the formation of a learning community among MSME actors that remains active after the activity.